Pedagogical Effectiveness of Arabic as a Foreign Language: A Comparative Perceptual Study of Teachers and Students in Islamic Senior High Schools - Abdurrahman, Abdurrahman; Syakhansyah, Zulfan (Kitaba, 2026)
This research is motivated by the persistently low communicative proficiency in Arabic among students in formal Islamic senior high schools (madrasahs), which stems from a fundamental perceptual disconnect between educators and learners. The primary objective of this study is to evaluate pedagogical effectiveness through a comparative analysis of teacher and student perspectives on instructional strategies, digital resources, and psycholinguistic barriers. Employing a mixed-methods approach with an explanatory sequential design, data were collected via Likert-scale questionnaires administered to 4 teachers and 15 students at MA Raudlatul Ulum Putra, followed by in-depth interviews, classroom observations, and documentation of instructional tools. The results reveal a statistically significant Methodological Perceptual Gap (p 0.05) across all measured indicators. Teachers perceive traditional grammar-based methods as highly effective, while students report high levels of language anxiety (M = 4.60), cognitive burnout from grammatical overload (M = 4.40, t = 6.25), and a strong desire for more communicative, engaging instruction. Furthermore, although digital facilities are physically available (p 0.05), their utilization remains minimal, creating a provision-utilization gap (p 0.05). The findings demonstrate that teachers and students operate within fundamentally different perceptual frameworks: teachers prioritize curricular completion and grammatical accuracy, while students value practical communication, active engagement, and psychological safety. This study makes three significant contributions: (1) it empirically documents the existence and magnitude of perceptual gaps in madrasah Arabic instruction; (2) it extends the affective filter hypothesis to the Islamic schooling context; and (3) it provides a strategic framework for curriculum revitalization. The findings underscore the urgent need for a paradigm shift from theoretical-scholastic orientations toward communicative-affective approaches, with implications for teacher training, digital integration, and language environment design.